Amycolatopsis anabasis sp. nov., a novel endophytic actinobacterium isolated from roots of Anabasis elatior. Issue 5 (4th May 2020) - Wang, Hong-Fei; Li, Xin-Yang; Gao, Rui; Xie, Yuan-Guo; Xiao, Min; Li, Qiu-Li; Li, Wen-Jun
Abstract : A novel endophytic actinobacterium, designated strain EGI 650086 T, was isolated from the roots of Anabasis elatior (C.A.Mey.) Schischk. collected in Xinjiang, north-west China. The taxonomic position of the strain was investigated using a polyphasic taxonomic approach. Growth occurred at 15–40 °C, pH 6.0–8.0 and in the presence of 0–6 % NaCl (w/v). Phylogenetic analysis based on 16S rRNA gene sequence and concatenation of 22 protein marker genes revealed that strain EGI 650086 T formed a monophyletic clade within the genus Amycolatopsis and shared the highest sequence similarities with Amycolatopsis nigrescens JCM 14717 T (97.1 %) and Amycolatopsis sacchari DSM 44468 T (97.0 %). Sequence similarities with type strains of other species of the genus Amycolatopsis were less than 97.0 %. The average nucleotide identity and DNA–DNA hybridization values between strain EGI 650086 T and the reference strains were 78.1–79.8 % and 22.1–23.0 %, respectively. The genome of strain EGI 650086 T was 10.9 Mb, with a DNA G+C content of 70.1 mol%. The diagnostic diamino acid in the peptidoglycan was meso -diaminopimelic acid. The major whole-cell sugars contained arabinose, galactose, glucose and ribose. The predominant menaquinones were MK-9 (H4 ) and MK-9 (H2 ). Major fatty acids were iso -C16 : 0 and summed feature 4 ( iso -C17 : 1 I and/or anteiso -C17 : 1 B). The polar lipid profile of strain EGI 650086 T included diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, hydroxy-phosphatidylethanolamine, phosphatidylinositol, phosphatidylinositol mannosides, two unknown phospholipids, an unknown glycolipid and an unknown lipid. Polyphasic taxonomic characteristics indicated that strain EGI 650086 T represents a novel species of the genus Amycolatopsis, for which the name Amycolatopsis anabasis sp. nov. is proposed. The type strain is EGI 650086 T (=KCTC 49044 T =CGMCC 4.7188 T ).